2019
DOI: 10.11604/pamj.2019.33.28.9448
|View full text |Cite
|
Sign up to set email alerts
|

L’observance thérapeutique: un autre défi à relever chez l’hémodialysé chronique

Abstract: La mauvaise observance thérapeutique (OT) est fréquemment rencontrée dans la plupart des maladies chroniques. Elle accroît la morbi-mortalité et les dépenses de santé. Les patients hémodialysés chroniques ont souvent une OT peu satisfaisante. L'objectif de notre étude était d'évaluer le niveau d'OT chez nos patients hémodialysés chroniques et d'identifier les facteurs prédictifs de mauvaise compliance. Nous avons réalisé une étude transversale en novembre 2011 au centre hospitalier d'Oujda. L'OT fût mesurée à … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
1
0
3
Order By: Relevance
“…Numerous studies, including ours, have established a direct correlation between low education levels and poor therapeutic compliance. Patients with limited cultural understanding often struggle to comprehend the importance of prescribed treatments 9 . Moreover, good therapeutic compliance is closely tied to technological means, where patients equipped with such technology can more effectively manage medication schedules, leveraging features like alarms on their mobile phones to prompt timely medication intake.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies, including ours, have established a direct correlation between low education levels and poor therapeutic compliance. Patients with limited cultural understanding often struggle to comprehend the importance of prescribed treatments 9 . Moreover, good therapeutic compliance is closely tied to technological means, where patients equipped with such technology can more effectively manage medication schedules, leveraging features like alarms on their mobile phones to prompt timely medication intake.…”
Section: Discussionmentioning
confidence: 99%
“…Le recours tardif à l'hémodialyse pourrait aussi expliquer le taux élévé de décès. Les insuffisants rénaux avec un niveau socio-économique bas ont moins accès aux structures de soins et commencent souvent tardivement la dialyse (Mhammedi et al, 2019).…”
Section: Discussionunclassified
“…Unfortunately, poor adherence is common among patients with chronic diseases, which increases the risk of morbidity and healthcare costs. Patients undergoing chronic hemodialysis often struggle with medication adherence, as per a study conducted by Mhammedi et al (2019). Furthermore, a study conducted in the United States found that non-adherence to hemodialysis increased the risk of mortality by 20% to 25% and the risk of hospitalisation by 16% (Mohamedi & Mosha, 2022).…”
Section: Discussionmentioning
confidence: 99%